Academic Supervision Model Based on Edmodo Application - Maria Marta Wulan Sukma Dewi; Yari Dwikurnaningsih; Marinu Waruwu (Journal of Education Technology, 2023)
The Covid 19 pandemic has had an impact on the implementation of academic supervision. This study aims to develop an online-based academic supervision model. The type of research conducted is research and development (Research and Development). The research subjects were 4 (four) school principals and 17 (seventeen) elementary school teachers. Data collection techniques used were interviews, documentation studies, and questionnaires. Qualitative data were analyzed using the Miles and Huberman model. Quantitative data obtained through a questionnaire. Quantitative data were analyzed by validation tests and limited trials using quantitative descriptive techniques with mean and percentage. The results showed that the MARIA academic supervision model (M - Mapping, A - Arranging the solution, R - Running the observation, I - Identifying the data, A – Acting the follow up) based on the Edmodo application has an impact on improving the performance of school principals and techers in elemantary schools, with the result of limited product trials on school principals at the 88% level and techers at the 86%  level with a very valid and feasible category to use. The implications of this research were facilitating the implementation of information technology-based supervision, improving the performance of school principals, increasing teacher competence in carrying out learning, and reducing teacher stress when supervised.